The life, times and work of William Gillies, 1898-1973 - McPherson, Andrew (Edinburgh University Press, 2024)
For seventy years, William Gillies has been seen as a placid painter of landscape and decorative still life. Andrew McPherson explodes this view to reveal a modernist whose response to the instabilities and violence of modernity touched universals of human experience. Gillies' idiom was shaped by institutions for artistic production unique to Scotland. But it was the politics of Scotland's connections to the rest of the British Isles that produced his mythic and misleading reputation. New paintings and new meanings are uncovered placing the micro-effects of modernity on mental health, family and community in the wider contexts of war, nationalism and public patronage. McPherson also shows how this changing world led Gillies towards new applications of modernist expression. Lavishly illustrated, and referencing almost one thousand works, this major reappraisal is an indispensable source on the cultural politics of a four-nation state and the reception of modernism in Britain
Keywords: Art, Scottish / 20th century; Modernism (Art) / Scotland; ART / European